Feasibility and Efficacy of a Psychological Therapy for Patients With a Schizophrenic Psychosis in an Inpatient Setting: Study Protocol of a Randomized Switch Controlled Trial - Redlich Bossy, Mona; Mueller, Daniel; Seifritz, Erich; Vetter, Stefan; Egger, Stephan T. (Frontiers in Public Health, 2020)
Background: Schizophrenic psychoses are severe mental disorders. Despite advances in treatment, outcomes are still unsatisfactory. Pharmacological treatments are still limited, in particular regarding improvements in psychosocial functioning and neuro-cognitive impairment. In recent years new psychological therapies have been developed, demonstrating promising results. However, most of these interventions have been designed for and studied in outpatients; their efficacy and feasibility for patients requiring hospitalization is still unknown. Therefore, we have designed a clinical trial to compare a neuro-cognitive (Integrated Neuro-cognitive Treatment INT); a cognitive-behavioral (Integrated Psychological Therapy IPT); and a control (Cogpack CGP) intervention for patients with a schizophrenic psychosis hospitalized for treatment. Methods: In a three-parallel-arm, single-blind, randomized, controlled study, we compare INT, IPT, and CGP. Participants will take part in two weekly sessions of one intervention for at least 16 sessions. If due to randomization, participants are allocated to a treatment arm not suitable for them, they are allowed to switch intervention after four sessions. Based on a sample size calculation, recruitment will continue until 30 participants have completed the intervention for each treatment arm. Outcome Measurement: Primary outcomes are: change in symptom as measured by the Positive and Negative Syndrome Scale (PANSS), change in psychosocial functioning as assessed by the mini ICF-APP and neuro-cognitive performance, assessed by the Matrics Cognitive Consensus Battery (MCCB). Other outcomes of interest are the Brief Symptom Inventory (BSI) and the Health of the Nation Outcome Scales (HoNOS); together with prescribed medication, treatment retention and completion rates. Outcomes will be measured at baseline, 2 weeks into treatment (prior to a potential switch of intervention arm), post-treatment and at 6 and 12-month post-treatment follow-ups. Expected Outcomes: We expect an overall improvement; however, with differences in specific domains for each treatment arm, with those completing INT showing better outcomes than IPT and CGP, respectively. We anticipate that lower functioning participants will drift to CGP and higher functioning participants to INT. Conclusion: Due to the complexity of treatment for patients with a schizophrenic psychosis, we consider it crucial to compare different treatment options for those more severely affected, therefore, requiring inpatient treatment. Trial registration:www.clinicaltrials.gov (ID: NCT03316664; 17.10.2017).